Characterization and Classification of Soils from Different Topographic Positions under Sugarcane Plantation in South Sulawesi, Indonesia - Risma Neswati; Christianto Lopulisa; Ahmad Faudzan Adzima (UNIVERSITY OF LAMPUNG, 2019)
The varied topography will influence the soil formation. This study aims to characterize and classify the soil selected on different topography positions of the sugarcane plantation area. The research was conducted in sugarcane plantation area of Camming, District of Bone, South Sulawesi, which was carried out from November 2017 to March 2018. This study used a descriptive method, observation and description of the nine soil profiles at three transects. Each transect consisted of three profiles points located in different positions, consisting of summit, backslope, and valleys. Each horizon soil samples were analyzed for their physical, chemical and micromorphology characteristics in the laboratory. Soil classification system was done by using soil taxonomy to the level of subgroups. The results showed that an average rainfall annual on the research location was 2.200 mm per year. Soil characteristics such as soil solum, cation exchange capacity, and sum of basic cations tended to increase in parts of the valley than in the back and summit. The primary mineral from the sand fraction included quartz, calcite, biotite, opaque, and orthoclase found especially in the position of the back and valley. The pore types consisted of vugh and packing void pores. Pedofeature type of soil was generally in the form of concretions and nodules that showed the process of oxidation and reduction. The soil type in the study area was classified into Typic Haplustepts and Typic Haplustalf.